HELPING PARENTS/CARERS TO GIVE MEDICINES TO CHILDREN IN HOSPITAL. Issue 9 (17th August 2016) - Williams, Lauren; Caldwell, Neil; Collins, Elizabeth
Abstract : Background: Medicines given to children in hospital are often prepared, checked and administered by two-registered nurses. Children are more likely to accept medicines given by a parent/carer1 but many hospital policies do not support such practice. Indeed the Trusts Medicines Management Policy allows single person medicines administration, except for children, but does not specify how medicine preparation and administration should take place or who should witness this. Our aim was to identify ways of increasing parent/carer involvement in giving medicines to children in hospital. Objectives: ▸ Measure time delays with the current administration process ▸ Identify obstacles that may prevent parent/carer involvement in giving medicines ▸ Identify how to overcome potential/perceived problems with parent involvement ▸ Determine parent/carer opinions of their involvement in giving medicines ▸ Assess single nurse checking and parent administration of medicines Method: Drug rounds were observed to identify time delays in medicines administration. A list of nineteen low risk medicines was proposed for parent administration with single nurse preparation. Focus groups were conducted, using structured questions, to get healthcare professionals perspective on the proposed changes and to approve a list of low risk medicines. Parents/carers were invited to complete a questionnaire regarding their involvement. Following Drug and Therapeutics Committee approval, parents/carers administered medicines with single nurse preparation during a trial period. Results: Administration of twenty-one medicines was observed under current practice. Delays were observed in all cases: average delay 6.5 minutes. Delays of 10 minutes were observed due to children fighting against having medicines administered by a nurse. Delays in 28% of cases were due to getting another nurse to check the preparation and seventeen of the twenty-one medicines observed where not in the medicines locker. Such delays often lead to parents administering medicines, despite the current policy not allowing such practice. Three focus groups, involving 12 staff, identified several problems and potential solutions to single nurse checking of medicines. The main concern was the risk of errors with dose calculations. Questionnaires were completed by 30 parents/carers and 97% wanted to be involved in administering medicines. The only parent/carer who did not, quoted: "My child will not take any medicine from me, this is part of the reason she has been admitted". Most parents/carers (80%) felt their child would be more at ease if they give the medicine. During the trial eight medicines were administered by parents and carers and no delays were observed. Conclusion: Children often receive late medicines in hospital. Parents/carers want to be involved in giving their child medicines. They suggest children would be more at ease. Parents/carer would also gain experience to help when administering medicines at home. Nurses support parent's being more involved in giving medicines. Focus groups suggest that medicines requiring dose calculations should be removed from a list of low risk medicines and parents be encouraged to administer medicines.